Cosmological Freedom and the Sons of Knowledge - Martinjak, Mikolaj (Studia Gdańskie, 2023)
Understanding what Gnosticism is and its interpretation depends on many factors. Commonly in many books, encyclopedias, and articles, it is often described as a dualistic system that separates body and mind, material and spiritual or knowledge and ignorance. This paper offers a brief overview and possible interpretations of two gnostic cosmogonical myths; Sethian, described in the Apocryphon of John and Valentinian myth found in Irenaeus’s Adversus Haeresies and Hippolytus’s Refutatio omnium haeresium. Those myths or cosmogonies are used as an example of the secret knowledge that could brings cosmological freedom. Events in the divine pleroma and actions of Sophia in myths are examined as the basis of a gnostic dogma that the sons of knowledge follow to achieve their freedom.